2018
DOI: 10.1080/10942912.2018.1560310
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and antioxidant properties of methanolic extract of root ofAsparagus racemosusLinn

Abstract: This study was to carry out phytochemical screening, to determine the total phenolic and flavonoid content as well as to evaluate the antioxidant properties of methanolic extract of root of Asparagus racemosus. Antioxidant properties were determined by 1,1-diphenyl,2-picrylhydrazyl (DPPH), hydroxyl radical, superoxide radical, hydrogen peroxide assay and total antioxidant activity by the phosphomolybdenum assay. The result showed that the powdered roots of A. racemosus were extracted with methanol and the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…The present study revealed potent inhibition of H 2 O 2 radicals by the extracts in a concentration-dependent manner, with lower IC 50 values obtained from the alcoholic extracts (about 4.7 and 3.2 µg/mL for the MEEI and EEEI extracts, respectively) compared to that from the apolar one (about 18.4 µg/mL). This data is in agreement with that achieved from the methanolic extract from E. compressa (about 2.8 µg/mL) [ 9 ] but considerably lower than that from the root of Asparagus racemosus Linn (about 27.6 µg/mL) [ 33 ]. Superoxide anion radicals are well known initiators of hydrogen peroxide or singlet oxygen in living systems [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study revealed potent inhibition of H 2 O 2 radicals by the extracts in a concentration-dependent manner, with lower IC 50 values obtained from the alcoholic extracts (about 4.7 and 3.2 µg/mL for the MEEI and EEEI extracts, respectively) compared to that from the apolar one (about 18.4 µg/mL). This data is in agreement with that achieved from the methanolic extract from E. compressa (about 2.8 µg/mL) [ 9 ] but considerably lower than that from the root of Asparagus racemosus Linn (about 27.6 µg/mL) [ 33 ]. Superoxide anion radicals are well known initiators of hydrogen peroxide or singlet oxygen in living systems [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…By getting an electron from an antioxidant molecule, DPPH • becomes diamagnetic by reduction into hydrazine derivative [ 36 ]. The MEEI extract presented very low IC 50 values (about 0.5 and 0.3 µg/mL for the DPPH • and the • OH scavenging assays, respectively) performing significantly better than ascorbic acid (about 2.6 and 2.3 µg/mL for the DPPH • and the • OH scavenging assays, respectively) and compared to the extracts from E. compressa (about 3.2 and 2.9 µg/mL, respectively) and Asparagus racemosus Linn (about 9.9 and 169.3 µg/mL, respectively) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity (IC 50 value) was found to be maximum in late monsoon and minimum in monsoon. It should be recognized that the lowest IC50 value shows the most powerful activity of anti-free radicals 54 . The rabbiteye blueberry leaves collecting in November had the maximum antioxidant capacity 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical analyses for major constituents were carried out based on the procedures of Harborne, 18 Fadeyi et al 19 and Tiwari. 20 The phytochemicals assessed were: Alkaloids, flavonoids, glycosides, tannins, saponins, triterpenoids compounds, phenols and steroids, and oxalate.…”
Section: Methodsmentioning
confidence: 99%